PEMANFAATAN SISTEM INFORMASI MANAJEMEN DI LEMBAGA CABANG DAN RANTING (LPCR) ORGANISASI “M” - Hendri Budi Utama (Jurnal Bahana Manajemen Pendidikan, 2019)
The purpose of this study is to provide information about the use of information systems in an organization. The development of science and information technology has indirectly changed the point of view and lifestyle of the people in carrying out their activities, one of which is the organization. Moreover, these organizations are large organizations such as M organizations, which have developed and have representation in all regions in Indonesia. Improving the performance of organizations in the future requires an information system and information technology. management information system is an information system designed to provide complete data as a basis for decision making in managerial activities. The use of management information systems in organization M has been applied well and maximally. The use of management information systems in M organizations has embodied a culture of collaboration within the organization. The management information system in organization M has become the foundation for leadership in taking policies / decisions.